PENGARUH MANAJEMEN PEMBELAJARAN DAN KOMPETENSI INSTRUKTUR TERHADAP MUTU LULUSAN LEMBAGA KURSUS DI KABUPATEN CIAMIS - Acim, Acim; Febriani, Vira; Rismayanti, Rismayanti (KHITABAH: Khazanah Penelitian Perbankan Syariah, 2025)
This study examines the influence of Learning Management and Instructor Competence on Graduate Quality at course institutions in Ciamis Regency. The urgency of this research is based on the demands for improving the quality of non-formal education as mandated by national education regulations, as well as the persistent inconsistency in the application of Learning Management and Instructor Competence levels among course institutions, which has the potential to affect graduate quality and public trust in the course institutions. This study uses a quantitative approach with a descriptive survey method. The data analysis techniques used include classical assumption test, correlation analysis, coefficient of determination, t-test, multiple linear regression, and F-test. The research population was all course institutions operating in Ciamis Regency, with samples determined using purposive sampling techniques. The results of the study indicate that: (1) Learning Management has a positive and significant effect on Graduate Quality; (2) Instructor Competence has a positive and significant effect on Graduate Quality and has a more dominant influence; and (3) Learning Management and Instructor Competence simultaneously have a significant effect on Graduate Quality. The implications of this study confirm that effective learning management supported by competent instructors is a key factor in improving the Quality of Graduates of course institutions, so it needs to be developed in an integrated and sustainable manner.